Development and validation of an immunoluminometric assay (ilma) for fetuin-a-glycoprotein - Bäumer, Amelie; Schmidt-Gayk, Heinrich; Aulmann, Michael; Kim, Ti-Sun (Journal of immunoassay & immunochemistry, 2009)
Background: To identify dialysis patients with low fetuin-A levels, a sensitive immunoluminometric assay (ILMA) was developed. Methods: For the two-site ILMA, one monoclonal antibody was coated to polystyrene beads and one polyclonal antibody was labelled with acridinium ester. Results: The lower detection threshold was 0.013 g/L, with the normal range 0.20-0.87 g/L (arithmetic mean 0.437 ± 0.118 g/L). Serum fetuin-A levels in the dialysis patients were significantly lower (arithmetic mean: 0.352 ± 0.099 g/L, p < 0.0001). Conclusion: This ILMA has been proved to be a reliable method for the determination of serum fetuin-A concentrations in dialysis patients.
Gesehen am 30.11.2022